HABITUS SUKU LAUT DALAM TRADISI MENONGKAH (Studi Pada Suku Laut di Desa Panglima Raja Kabupeten Indragiri Hilir) - Era Hartati; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
YouTube is an application or social media platform that provides variant kind of video with different content in it. The content in YouTube such as mystic, gaming, cooking and others are always attracting for YouTube user. One of a very unique and favorable content by lots of people is mystic content that Risa and her cousins always bring. The aim of this study is to find out either there is an effect or not of jurnalrisa’s YouTube channel content on subscriber’s opinion about mistic content.This study use quantitative explanative method with random sampling technique to 400 respondents. This study examined using the data that has been shared thourgh online with google form with link: bit.ly/kuisionerjurnalrisa. After giving out the questionnaire through Google form, researcher analysis the data with SPSS application for windows 25 version, linear regreassion analysis. Where jurnalrisa’s YouTube channel content as X variable and subscriber’s opinion as Y variable.The result of this research is there is an effect of jurnalrisa’s YouTube channel content on subscriber’s opinion about mystic content, which on the result of simple linear regression analysis, the regression coefficient value obtained in this study is Y = 7,755 + 0,570 X. H0 is rejected and Ha is accepted with a significance level 0,000. If the significance level is smaller than the standard significance 0,05, we can conclude there is an effect of jurnalrisa’s YouTube channel content on subscriber’s opinion about mystic content.  The coefficient of determination R square in this study amounted 42,2% that shows the number of efect from jurnalrisa YouTube channel content on subscriber opinion about mystic content is in medium category. While th remaining percentage 57,8% is influenced by other variables that not included in this study.                                       Keywords: effect, content, YouTube, mystic, jurnalrisa